Dorsolateral prefrontal cortex metabolites and their relationship with plasticity in Alzheimer's disease: Biomarkers (non‐neuroimaging) / novel biomarkers. (7th December 2020) - Kumar, Sanjeev; Iwata, Yusuke; Zomorrodi, Reza; Blumberger, Daniel M.; Fischer, Corinne E.; Daskalakis, Zafiris J.; Mulsant, Benoit H.; Pollock, Bruce G.; Graff‐Guerrero, Ariel; Rajji, Tarek K.
Abstract: Background: Previous studies have shown that patients with Alzheimer's disease (AD) present with deficits in neuroplasticity of their dorsolateral prefrontal cortex (DLPFC); and decreased N‐acetyl aspartate (NAA) and increased myo‐inositol (mI) concentrations in the cingulate cortex and hippocampus. In this study, we examined the relationship between these metabolites and neuroplasticity in the DLPFC of patients with AD and healthy older adults. Method: Patients meeting the core clinical criteria for probable AD and older healthy controls (HC) were recruited. Left DLPFC plasticity was assessed using paired associative stimulation (PAS) combined with EEG. NAA and mI concentrations were assessed in the DLPFC using 3T proton Magnetic Resonance Spectroscopy (point‐resolved spectroscopy, echo time = 35 ms). Result: 48 AD participants (mean (SD) age: 75.4 (6.9) years; mean (SD) Mini Mental State Examination (MMSE) score (SD): 23.1 (3.1)) were compared with 27 HC (mean (SD) age: 72.3 (7.0) years; mean (SD) MMSE: 29.5 (0.6)): participants with AD had impaired DLPFC plasticity (t = 2.8, df = 69, p = 0.006) and decreased NAA concentration in the DLPFC (t = 2.4, df = 64, p = 0.02). In the combined group of AD and HC participants, after correcting for multiple comparisons, mI concentration in the DLPFC was negatively correlated with DLPFC plasticity (Pearson's r = ‐ 0.4, n = 62, p corrected = 0.002). Conclusion: Deficits in neuroplasticity in the DLPFC of patients with AD are associated with abnormalities of a metabolite indicative of neuronal injury. These findings advance our understanding of potential mechanisms underlying deficits in DLPFC plasticity in AD.